2022
DOI: 10.3389/fpsyg.2022.909842
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and Validation of a Scale for Measuring the Curriculum-Based Professional Learning Community in Early Childhood Education in China

Abstract: Teachers' professional learning community, as an effective path to promote teachers' professional development and elevate teaching quality, has been widely used in school contexts. In preschools, the practice of teachers' professional learning community mainly focuses on the curriculum in early childhood education. The revision and adaptation of the scale of the professional learning community for preschool teachers in the Chinese cultural context are of great significance for understanding the current situati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…In the context of education, Leithwood (1994) clearly proposed that the transformational leadership style in schools could promote teachers' identification with organizational goals by building a cooperative institutional culture, motivating teachers to develop continuously, and ultimately achieving the development and reform of schools. Transformational leadership, according to Peng et al (2022), enhanced teachers' work satisfaction through PLCs. Additionally, some studies have indicated that the transformational leadership style of preschool principals can improve teachers' collective efficacy (Dussault et al, 2008), stimulate teachers' professional learning and motivation (Thoonen et al, 2011), and promote the development of teacher leadership (Li and Liu, 2020).…”
Section: Principal Leadership Stylementioning
confidence: 99%
See 1 more Smart Citation
“…In the context of education, Leithwood (1994) clearly proposed that the transformational leadership style in schools could promote teachers' identification with organizational goals by building a cooperative institutional culture, motivating teachers to develop continuously, and ultimately achieving the development and reform of schools. Transformational leadership, according to Peng et al (2022), enhanced teachers' work satisfaction through PLCs. Additionally, some studies have indicated that the transformational leadership style of preschool principals can improve teachers' collective efficacy (Dussault et al, 2008), stimulate teachers' professional learning and motivation (Thoonen et al, 2011), and promote the development of teacher leadership (Li and Liu, 2020).…”
Section: Principal Leadership Stylementioning
confidence: 99%
“…The transformational leadership style of principals also indirectly affects the leadership of preschool teachers through the mediating role of psychological capital. Transformational leadership emphasizes sharing and the development of teachers' collective capacity (Gkolia et al, 2018), which is often reflected in the professional learning community (PLC) of preschool teachers (Peng et al, 2022). In a professional learning community, the charismatic influence of the director and the motivation of good prospects can make preschool teachers feel a sense of belonging and identification with the organization and maintain a positive psychological state in their work.…”
Section: Relationship Between Preschool Principal Leadership Styles T...mentioning
confidence: 99%